f(x) = 4/(x-1)
g(x) = 2x
f[g(x)] = f(2x) = 4/(2x – 1)
g[f(x)] = g(4/x-1) = 2(4/x-1) = 8/(x-1)
4/(2x-1) = 8/(x-1)
=> 1/(2x-1) = 2/(x-1)
x – 1 = 4x – 2
3x = 1
x = 1/3
f(g(x)) = 4/(2x) – 1 = 2/x – 1
g(f(x) = 2(4/x – 1) = 8/x – 2
so you are asking
2/x – 1 = 8/x – 2
2/x – 8/x = -1
-6/x = -1
x = 6
unless your problem is
f(x) = 4/(x-1) and g(x) = 2x
then
f(g(x)) = 4/(2x – 1)
g(f(x)) = 2(4/(x-1) = 8/(x-1)
so the problem would then be
4/(2x-1) = 8/(x-1)
cross multiply
4(x-1) = 8(2x-1)
4x – 4 = 16x -8
-12x = -4
x = 1/3
f(g(x)) = (4/2x) – 1 = 2/x – 1
g(f(x)) = 2[4/x – 1] = 8/x – 2
set them equal to find the solution set
[2/x – 1] = [8/x – 2]
multiply both sides by x
2 – x = 8 – 2x
x = 6
Latest posts by Answer Prime (see all)
- What is the average mass of a single sulfur atom in grams - January 27, 2023
- How many smaller rectangles are there in an area model that represents 27X83? - January 27, 2023
- Why Do You Need To Hire a Professional Translator for Your Company? - January 27, 2023